The Effects of an End-of-life Care Program on The Palliative Care Outcomes and Perceived Peaceful End of Life Among End-stage Cancer Patients - Anseekaew, Patchareerat; Matchim, Yaowarat; Ratanabunjerdkul, Hataiwan (Journal of The Royal Thai Army Nurses, 2020)
This study aimed to examine the effects of an end-of-life care program on the palliative care outcomes and perceived peaceful end of life among end-stage cancer patients. The participants were selected based on inclusion including 32 end-stage cancer patients and 32 family caregivers. The participants received the 1-week end-of-life care program that was developed by the researcher based on the theory of a peaceful end of life of Ruland and Moore. Data were analyzed using paired t–test. The results showed that, after the intervention completing, the mean score for the palliative care outcomes as perceived by the end-stage cancer patients and that as perceived by the family caregivers decreased with a statistically-significant difference when compared to those at baseline (t = -5.90, p < .001; t = -7.72, p < .001). The mean score for peaceful end of life as perceived by the end-stage cancer patients and that as perceived by the family caregivers increased with a statistically-significant difference when compared to those at baseline (t = 7.90, p < .001; t = 8.79, p < .001). The results of the study indicated that the 1-week end-of-life care program which was developed based on the theory of peaceful end of life by Ruland and Moore cooperating with family caregivers can enhance positive palliative care outcomes and promote the peaceful end of life of end-stage cancer patients. Healthcare providers can implement this program for end-stage cancer patients in other contexts.